Diagnostic Approach of Atypical Cells in Effusion Cytology Using Computerized Image Analysis - Al-Obaidi, Zainab A J (AL-Kindy College Medical Journal, 2007)
Background: Cytology is one of the important diagnostic tests done on effusion fluid. It can detect malignant cells in up to 60% of malignant cases. The most important benign cell present in these effusions is the mesothelial cell. Mesothelial atypia can be striking andmay simulate metastatic carcinoma. Many clinical conditions may produce such a reactive atypical cells as in anemia,SLE, liver cirrhosis and many other conditions. Recently many studies showed the value of computerized image analysis in differentiating atypical cells from malignant adenocarcinoma cells in effusion smears. Other studies support the reliability of the quantitative analysisand morphometric features and proved that they are objective prognostic indices. Methods: Sixty three cases of pleural and peritoneal smears, previously reported as benign (19) cases, malignant (21) cases or atypical (23) cases, were retrieved from the files. In each of these smears; nuclear area, perimeter, and roundness coefficient of 80-100 cell were determined at x400 magnification by the use of image analysis system. Statistical analysis was performed using analysis of variance and Tukey’s HSD test. Results: The mean values of nuclear roundness, nuclear perimeter and nuclear area vary between the three groups (benign, atypical and malignant cells) by using analysis of variance (p > 0.01). The value of nuclear roundness, perimeter and area did not differ significantly between benign and atypical cells (Tukey’s test: p<0.01). On the other hand, the value of nuclear roundness, perimeter and area showed a significant difference between malignant and atypical cells(Tukey’s test: p> 0.01). Conclusion: In conclusion, our data suggest that cytomorphometry performed on effusion smear cells may provide important information for the differentiation of atypical cells from malignant cells, in which the values of atypical cells are closer to those of benign cells during the examination of pleural and peritoneal smears by the use of image analysis system